PERSEPSI MASYARAKAT DALAM PENGELOLAAN LIMBAH ORGANIK RUMAH TANGGA MENJADI PUPUK RAMAH LINGKUNGAN DI DESA DUSUN TUA KABUPATEN INDRAGIRI HILIR - Nababan, Bunga; Desti, Desti; Hidayati, Nurkhairo (Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to analyze the knowledge, attitudes, village support, and availability of facilities and information among the community of Dusun Tua Village in managing household organic waste into environmentally friendly fertilizer. The research employed a mixed methods approach, using quantitative instruments in the form of questionnaires divided into four main variables, as well as qualitative interviews with purposively selected informants. The quantitative sample consisted of 30 respondents, who were heads of households or individuals directly involved in household waste management. The results indicate that the level of community knowledge is in the moderate category, community attitudes and village support are classified as high, while the availability of facilities and information remains low. Qualitative findings strengthen the quantitative data by revealing barriers and community needs in the practice of organic waste management. These findings provide recommendations for strengthening education, improving the provision of facilities, and enhancing village policies to support sustainable waste management.